(untitled) (Biological Sciences - PJSIR, 2004)
Traffic noise survey was conducted at 15 sites in the different residential and commercial areas of Lahore city and at each survey site, noise data were collected from 0900 to 1700 h. The data collected have been analyzed for the recorded range, LA99, LA90, LA50, LA10 and LA1 and approximate vales of LAeq8h were evaluated for each survey site. The results are discussed with reference to some criteria for community annoyance and ways and means to limit high-level traffic noise are suggested.